2011
DOI: 10.1016/j.jtcvs.2011.04.048
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve surgery: Marked increases in volume and significant decreases in mechanical valve use—an analysis of 41,227 patients over 5 years from the Society for Cardiothoracic Surgery in Great Britain and Ireland National database

Abstract: We have seen a large increase in annual volume of aortic valve replacements, with more patients undergoing surgery for aortic stenosis and an increase in surgery in the elderly and high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
127
0
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(146 citation statements)
references
References 24 publications
10
127
0
9
Order By: Relevance
“…by guest on May 11, 2018 http://circinterventions.ahajournals.org/ Downloaded from Renal Dysfunction Impacts on TAVI Outcomes was set at P≤0.05 (2-tailed). Heterogeneity was assessed by Qstatistic and I 2 tests.…”
Section: What the Study Addsmentioning
confidence: 99%
“…by guest on May 11, 2018 http://circinterventions.ahajournals.org/ Downloaded from Renal Dysfunction Impacts on TAVI Outcomes was set at P≤0.05 (2-tailed). Heterogeneity was assessed by Qstatistic and I 2 tests.…”
Section: What the Study Addsmentioning
confidence: 99%
“…Approximately 280.000 heart valve replacements are performed each year (Pibarot and Dumesnil, 2009) and this number still increases (Takkenberg et al, 2008;Dunning et al, 2011). Currently, diseased valves are replaced by either mechanical or bioprosthetic valves.…”
Section: Introductionmentioning
confidence: 99%
“…The annual number increased by 20%, with significant increases in the mean age of patients with aortic stenosis, octogenarians, the proportion of high-risk patients and again those receiving biological valves (which is almost certainly influenced by surgeons' views of better longevity of modern biological valves and the promise of a transcatheter valve solution for subsequent valve failure) (47). Over this time, in-hospital mortality decreased from 4.4% to 3.7% (48). While transcatheter valve insertion (TAVI) (see below) is having an impact on valve surgery, in contract to just eroding the numbers of conventional valve operations, it has been reported that starting a TAVI service may increase overall aortic valve interventions, including those for conventional surgery (49).…”
Section: Aortic Valve Surgerymentioning
confidence: 99%